High-Intensity Focused Ultrasound Ablation for Unresectable Primary and Metastatic Liver Cancer: Real-World Research in a Chinese Tertiary Center With 275 Cases - Ji, Yongshuo; Zhu, Junqiu; Zhu, Linglin; Zhu, Yanfei; Zhao, Hong (Frontiers in Oncology, 2020)
Patients with liver cancer who received HIFU ablation were included in this analysis, including PLC cohort (n=80) and MLC cohort (n=195). The primary endpoint of our research was tumor response. The secondary endpoints included survival outcomes (OS), VAS pain scores, AFP reliefs, and complications. ORR and DCR were observed to be 71.8% and 81.2%, respectively in patients with HCC, and were 63.7% and 83.2% in cases with MLC. AFP levels and VAS levels significantly decreased after HIFU treatment comparing with the baseline levels in patients with HCC (p<0.05). Median overall survival was estimated to be 13.0 and 12.0 months in PLC and MLC cohort. The 1-year survival rate was 70.69% and 48.00%, respectively. Multivariate regression analysis showed that VAS ≥ 5 and LDi ≥ 5 cm were the independent risk factors for the poor survival in PLC. For patients with MLC, independent risk factors were identified as VAS ≥ 5, LDi ≥ 5 cm, existence of extrahepatic metastases, and time to HIFU treatment from diagnosis < 3 months. No severe adverse events (AEs) were reported. In conclusion, HIFU ablation might be one of the effective and safe options for patients with liver cancer regardless of primary and metastatic lesions.